D Development of Junior High School Science E-Module Integrated with Socio-Cultural of Balinese Society to Improvw Students Science Literacy - Putu Henrika Utari; I Wayan Subagia; Anak Agung Istri Agung Rai Sudiatmika (Jurnal Penelitian Pendidikan IPA, 2024)
The research aimed at analyzing and explaining the validity, practicality, and effectivity of e-module science for junior high school integrated with the Balinese Socio-Cultural to improve students' scientific literacy. This research and development were modified from Borg Gall and Thiagarajan’s models. The research design used the effectiveness of the e-module was One Group Pretest Posttest Design. The instruments used were expert validation questionnaires, practicality questionnaires, and scientific literacy tests. Development stages of the e-module development consisted of 1) data collection, 2) product design, 3) product development, 4) limitary out, 5) product test theoretically, 6) empirical product test, and 7) product finalization. The results show that 1) the e-module is valid from a material point of view with very good qualifications, language validity with very valid qualifications, the validity of media with very good qualifications, and suitability of Balinese culture with very valid qualifications, 2) e-module is very practical to be used on the field, and 3) e-module is effective to improve the scientific literacy of students